Child Neurology: Siblings with infantile epilepsy and developmental delay. (17th July 2018) - Liu, Yin; Michelson, David; Clark, Robin; Gold, June-Anne
Abstract : Objective: Chromosome 14q11-q22 deletion syndrome (OMIM 613457) is a rare genomic disorder with a variable phenotype. Methods: We report 2 full siblings, a brother and sister, with a unique familial 2.4 Mb microdeletion at 14q13.1–14q13.3 by microarray (first identified in the brother, Mayo Clinical Laboratories, 2010). Results: Both children presented with infantile spasms that evolved to intractable epilepsy and profound developmental delay. They share distinctive dysmorphic features: long expressionless facies, full cheeks, flattened midface, full lips, and generalized hypotonia. Only the sister has hemophagocytic lymphohistiocytosis (HLH). Testing in the brother revealed 3 variants of unknown significance (VUS) (Greenwood Genetics, epilepsy/seizure panel, 145 genes, 2015). The sister had normal results with a different gene panel (GeneDx, infantile epilepsy panel, 75 genes, 2016) but it did not include the 3 genes in which VUS were identified in her brother. Whole exome sequencing in the mother, father, and both siblings was negative without VUS (GeneDx, XomeDx, 2016). There were no variants within the deleted interval in the intact allele for both children. Parental fluorescent in situ hybridization studies for 14q13.1–14q13.3, done in 2017, were normal. Haplotype analysis of the intact chromosome 14 in the sister supported paternal origin for the deletion and likely germline mosaicism in the father. Haploinsufficiency of genes in the deleted region has not been associated with an abnormal phenotype. Conclusions: These children have a specific, recognizable neurodevelopmental phenotype and 14q13 microdeletion. This report highlights the challenges of coordinating and interpreting genetic testing in syndromic epilepsy.